PENGGUNAAN APLIKASI E- AUDIT DALAM SISTEM INFORMASI MANAJEMEN INSPEKTORAT POLRI - Pramuja Sigit Wahono; Safuan Safuan; Musa Alkadhim Alhabshy (Jurnal Ilmiah Global Education, 2023)
This research investigates the utilization of e-audit applications in the management information system of the Indonesian National Police Inspectorate. The Inspectorate plays a crucial role in upholding the integrity and efficiency of the Republic of Indonesia Police. However, the manual audit process faces challenges in terms of accuracy, efficiency, and standardization. Therefore, the utilization of e-audit applications is seen as a potential solution to enhance the effectiveness and efficiency of the audit system.This study employs a mixed-methods approach that combines literature review, observation, interviews, and surveys. The literature review provides an understanding of the utilization of e-audit applications and management information systems in the context of the Inspectorate. Observations and interviews were conducted to observe the existing audit processes and gain direct insights from auditors and Inspectorate staff. Surveys were utilized to collect data on users' perceptions and experiences with e-audit applications. The findings indicate that the utilization of e-audit applications can enhance the efficiency, accuracy, and consistency of the audit process. E-audit applications enable process automation, accurate data collection, quick analysis, and efficient report generation. However, the implementation of e-audit applications also faces challenges such as the need for deep understanding, staff competence development, and adequate information technology infrastructure. This research contributes to understanding the role and benefits of utilizing e-audit applications in the management information system of the Inspectorate. Recommendations are provided to strengthen awareness and understanding, enhance staff competence, and overcome information technology infrastructure constraints. It is expected that the utilization of e-audit applications can improve the overall quality of internal supervision and transparency within the Indonesian National Police.